1990
DOI: 10.1021/j100381a036
|View full text |Cite
|
Sign up to set email alerts
|

Bistability and oscillations in the electrocatalyzed oxidation of formaldehyde

Abstract: A variety of nonlinear phenomena, which was observed during the electrochemical oxidation of formaldehyde at a rotating platinum disk, is described. The experiments were conducted under galvanostatic conditions and the applied current was treated as a bifurcation parameter. The oxidation process exhibited bistability; both high-potential and low-potential states were found within the same range of values of current. However, most of the low-potential stationary behavior was either nonexistent or unstable in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…Although the regeneration oscillation may be one of mixed-mode oscillations, 18,19 it has a distinctive feature that the metastable high potential is higher than 1.0 V, which potential value is a sign of the cease of ordinary oscillations, and the duration of the metastable state is long, sometimes longer than 1 h, as shown later. The regeneration oscillation is similar to the "drastically" changed oscillation observed by Chen et al 31,32 with 5.0 © 10 ¹6 M chloride ions and 0.10 M HCOONa in a 0.50 M perchloric acid solution at room temperature, although the duration of the high potential state is very short.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Although the regeneration oscillation may be one of mixed-mode oscillations, 18,19 it has a distinctive feature that the metastable high potential is higher than 1.0 V, which potential value is a sign of the cease of ordinary oscillations, and the duration of the metastable state is long, sometimes longer than 1 h, as shown later. The regeneration oscillation is similar to the "drastically" changed oscillation observed by Chen et al 31,32 with 5.0 © 10 ¹6 M chloride ions and 0.10 M HCOONa in a 0.50 M perchloric acid solution at room temperature, although the duration of the high potential state is very short.…”
Section: Resultsmentioning
confidence: 68%
“…It is also established [14][15][16][17] that the indirect path involves adsorbed CO in common for oxidations of the three C 1 -compounds. It is well known 8,[18][19][20][21][22] that adsorbed CO plays a crucial role in the oscillation. Gojuki et al 9 have recently proposed that adsorbed water is also involved in the oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…In the above cited work, Xu and Schell [65] have reported the period-doubling phenomena, In more recent studies, the single-crystal, low-index Pt electrodes were employed, for which the oscillatory instabilities were reported under potentiostatic conditions and discussed in terms of several possible mechanisms [26,[71][72][73][74][75][76]. In these papers a very rich set of experimental data was collected, including the role of concentration of formic acid, the magnitude of ohmic drops, and of the solution stirring intensity.…”
Section: Experimental Results and Outline Oscillation Mechanismmentioning
confidence: 99%
“…Later studies of the oscillations and bistability on solid electrodes were reported by Wojtowicz et al [61], Bockris et al [63], and Schell et al [64][65][66][67]. In addition to classical electrochemical methods, Inzelt and Kertész [68] have employed electrochemical quartz crystal microbalance (EQCM) technique to show that the potential oscillations in the course of galvanostatic oscillations of formic acid at Pt electrode are associated with accumulation and consumption of strongly bound species.…”
Section: Experimental Results and Outline Oscillation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation